2020
DOI: 10.3390/s20154123
|View full text |Cite
|
Sign up to set email alerts
|

LoRa Traffic Generator Based on Software Defined Radio Technology for LoRa Modulation Orthogonality Analysis: Empirical and Experimental Evaluation

Abstract: The digital revolution has changed the way we implement and use connected devices and systems by offering Internet communication capabilities to simple objects around us. The growth of information technologies, together with the concept of the Internet of Things (IoT), exponentially amplified the connectivity capabilities of devices. Up to this moment, the Long Range (LoRa) communication technology has been regarded as the perfect candidate, created to solve the issues of the IoT concept, such as scalability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The authors assume that all the IoT devices have the same traffic generation method, and the SF allocation considers Intra and inter SF collisions probability. This work proposed an ILP model that considers the IoT devices' physical locations and the imperfect SF orthogonality, increasing the transmission success probability to each IoT node [85]. The simulation results demonstrate the effectiveness of their resource allocation for the scenario with different LoRaWAN gateways.…”
Section: One Parametermentioning
confidence: 95%
See 1 more Smart Citation
“…The authors assume that all the IoT devices have the same traffic generation method, and the SF allocation considers Intra and inter SF collisions probability. This work proposed an ILP model that considers the IoT devices' physical locations and the imperfect SF orthogonality, increasing the transmission success probability to each IoT node [85]. The simulation results demonstrate the effectiveness of their resource allocation for the scenario with different LoRaWAN gateways.…”
Section: One Parametermentioning
confidence: 95%
“…However, recent studies [85,89,95,96,97,98] evaluated the effects of inter-SF interference and concluded that SFs adopted by LoRa are quasi-orthogonal. For instance, Lavric et al [85] conducted an empirical and practical evaluation and concluded that collisions between different SF within the same communication channel occur, drastically decreasing the LoRaWAN performance. This decrease occurs because collisions lead to the gateway not receiving packet transmissions using different SFs [96].…”
Section: Summary and Open Issuesmentioning
confidence: 99%
“…LoRa is developed for supporting the LPWAN (Low Power Wide Area Network) that utilizes the ISM (Industrial, Scientific, Medical) bands of 433 MHz (Asia), 915 MHz (North America), and 868 MHz (Europe) [ 13 ]. LoRa modulation is formed from the CSS (Chirp Spread Spectrum) that provides robustness in case of multipath propagation interferences [ 30 ]. LoRa modulation is customized on distinct parameters, like spreading factor (SF), code rate (CR), and bandwidth (BW).…”
Section: Overview Of Loramentioning
confidence: 99%
“…Meanwhile, LoRa technology uses different spreading factors to increase the number of nodes in the channel, which is the use of orthogonality of different spreading factors. However, the experimental results in [ 25 ] show that different spreading factors will also exhibit conflict and greatly reduce the performance of LoRa. Moreover, the author believes that the packet length is not a key factor affecting the performance of LoRa.…”
Section: Related Workmentioning
confidence: 99%